2018
DOI: 10.4103/ijmbs.ijmbs_75_18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse in graves' hyperthyroidism after treatment with antithyroid drugs

Abstract: Original Article introduCtionGraves' hyperthyroidism is the most common cause of hyperthyroidism. [1] Treatment options include antithyroid drugs (ATDs), radioactive iodine, or surgical resection, although none of these options target the mechanism of the disease, and there is no single treatment that can target both hyperthyroidism and the main extrathyroidal manifestation (orbitopathy). [2] ATDs act by inhibiting thyroid hormone synthesis, but they have some immunosuppressive action. In Europe and Japan, ATD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Additionally, Struja et al. ( 32 ) conducted a systematic review and meta-analysis, which supports our study findings. They found that the addition of immunosuppressive drugs to standard GD treatment can significantly reduce the risk of relapse in GD patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, Struja et al. ( 32 ) conducted a systematic review and meta-analysis, which supports our study findings. They found that the addition of immunosuppressive drugs to standard GD treatment can significantly reduce the risk of relapse in GD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Randomization is a key feature of clinical trials that helps to minimize bias and ensure that the treatment groups are comparable. However, a limitation of the study is that the follow-up period was only 12 months after the cessation of treatment, which may have been relatively short to evaluate long-term remission status, even though most GD recurrences tend to occur within the first 12 months after ATD withdrawal ( 32 , 36 ). Also as, there was no blinding of participants or researchers there might be an unintentional influence on the study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared with rates from previous studies in Europe and Africa, the relapse rate was 30 -49% after one year of discontinuation. [28][29][30] The clinical factors related to relapse were < 40 years of age; smoking; TAO; thyroid size by ultrasound; serum FT4, FT3, and TRAb levels; and total T4 levels ≥ 2 times the upper normal range. 30 The clinical factors related to remission were female sex, nonsmoking status, no TAO and duration of treatment of more than 2 years.…”
Section: Gd Patient Baseline and Clinical Characteristics In The Relapse And Remission Groupsmentioning
confidence: 99%
“…[28][29][30] The clinical factors related to relapse were < 40 years of age; smoking; TAO; thyroid size by ultrasound; serum FT4, FT3, and TRAb levels; and total T4 levels ≥ 2 times the upper normal range. 30 The clinical factors related to remission were female sex, nonsmoking status, no TAO and duration of treatment of more than 2 years. 28 This study showed a relapse rate similar to that of previous studies and confirmed that some clinical risk factors influence relapse in both Asian and Western countries.…”
Section: Gd Patient Baseline and Clinical Characteristics In The Relapse And Remission Groupsmentioning
confidence: 99%
See 1 more Smart Citation